2017
DOI: 10.5498/wjp.v7.i2.106
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and factors associated with depression among inpatients with cardiovascular disease

Abstract: AIMTo identify factors associated with depressive symptoms among inpatients with cardiovascular disease (CVD).METHODSThis is a cross-sectional study performed in a subsample of a large cross-sectional research that investigated affective disorders and suicide behaviour among inpatients hospitalized in non-surgical wards of the University Hospital of the Federal University of Minas Gerais from November 2013 to October 2015. Sociodemographic and clinical data were obtained through a structured interview and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(55 reference statements)
0
5
1
Order By: Relevance
“…Level of subjective social status was moderate in the sample ( M = 5.7, SD = 2.0) with AA women reporting lower levels of ( M = 5.2, SD = 2.2) compared to their NHW counterparts ( M = 6.2, SD = 1.6), F (1,96) = 7.2, p = 0.009. The means observed for the CTQ scales were higher than those reported in older adults 61 and there were no significant differences between AA and NHW for any of the CTQ subscales. The mean CES-D score (M = 11.6, SD = 9.1) was low with no differences between AA and NHW women in depressive symptoms.…”
Section: Resultscontrasting
confidence: 67%
“…Level of subjective social status was moderate in the sample ( M = 5.7, SD = 2.0) with AA women reporting lower levels of ( M = 5.2, SD = 2.2) compared to their NHW counterparts ( M = 6.2, SD = 1.6), F (1,96) = 7.2, p = 0.009. The means observed for the CTQ scales were higher than those reported in older adults 61 and there were no significant differences between AA and NHW for any of the CTQ subscales. The mean CES-D score (M = 11.6, SD = 9.1) was low with no differences between AA and NHW women in depressive symptoms.…”
Section: Resultscontrasting
confidence: 67%
“…Our results may serve as a useful foundation for further research on the complex etiologic factors and sequelae of this mental disorder, as well as on the causal mechanisms underlying the associations found in this study. It is important for future studies to establish whether the observed increased health problems follow causally from depression, stem from shared genetic [33][34][35] or environmental risk factors, 36,37 or whether the associations are due to reverse causality. Furthermore, these results could guide clinical intervention, risk assessment, and prediction tools tailored to young patients with depression.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Four studies included patients with "cardiac diagnoses," which included CHD, HF, atrial fibrillation, and/or arrythmia. [49][50][51][52] One study examined patients who were admitted to a cardiac rehabilitation program with a cardiac diagnosis. 53…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Details on validity and reliability of each resilience scale are provided in Table 1. Five studies used the Wagnild and Young Resilience Scale, either 13-, 14-, or 25-item versions, [47][48][49]51,52,54 first established from a qualitative study of 24 women who had adapted successfully after a major adverse event. 61 From their narratives, 5 interrelated components were identified that constitute resilience: equanimity, perseverance, self-reliance, meaningfulness, and existential aloneness.…”
Section: Resiliencementioning
confidence: 99%